Economic evaluation of border closure for a generic severe pandemic threat using New Zealand Treasury methods. (8th August 2018) - Boyd, Matt; Mansoor, Osman D.; Baker, Michael G.; Wilson, Nick
Abstract: Objective: To perform a comprehensive economic evaluation of border closure for an island nation in the face of severe pandemic scenarios. Methods: The costing tool developed by the New Zealand (NZ) Treasury (CBAx) was used for the analyses. Pandemic scenarios were as per previous work; 1 epidemiological data were from past New Zealand influenza pandemics. Results: The net present value of successful border closure was NZ7.86 billion for Scenario A (half the mortality rate of the 1918 influenza pandemic) and 144 billion for preventing a more severe pandemic (10 times the mortality of scenario A). Cost–utility analyses found border closure was relatively cost‐effective, at 14, 400 per QALY gained in Scenario A, and cost‐saving for Scenario B (taking the societal perspective). Conclusions: This work quantifies the economic benefits and costs from border closure for New Zealand under specific assumptions in a generic but severe pandemic threat (e.g. influenza, synthetic bioweapon). Preparing for such a pandemic response seems wise for an island nation, although successful border closure may only be feasible if planned well ahead. Implications for public health: Policy makers responsible for generic pandemic planning should explore how border closure could be implemented, including practical and legal frameworks.